Simulating large DNA nanostructures with a coarse-grained model - Snodin, B (2016)
In this thesis we investigate the self-assembly and structural properties of DNA origamis, which are large-scale DNA nanostructures comprising thousands of DNA base pairs, using the coarse-grained model of DNA called oxDNA. We use simulations of oxDNA, with both a "brute-force" approach and with a rareevent method, to probe how the origamis self-assemble from single strands of DNA in solution. With the brute-force approach we are able to simulate the complete assembly of a small 384-base-pair origami at a high strand concentration, and identify kinetic traps under certain conditions, as well as cooperativity between staple strands and optimal assembly windows. These findings help to rationalise certain successful design strategies. Using the rare-event method we are able to use the lower strand concentrations typical of experimental conditions and make more quantitative measurements, identifying sequential staple binding for our origami design at these conditions, and probing how a staple binds each of its domains. We introduce oxDNA2, an enhanced version of oxDNA, which has improved predictive power for origami structure, as well as other improvements such as salt dependence. We verify that the model reproduces well the structural properties of Holliday junctions, which are a vital feature of DNA origamis. We then use the model to investigate the basic structural properties of 2D and 3D origamis, characterising their generic structural features such as, for 2D structures, the "weave pattern," where adjacent double helices push apart away from the junctions, and "corrugation," a systematic, out-of-plane bending of the double helices. We find a good agreement with experiment where data is available.